Pengaruh muatan dan kecepatan kendaraan terhadap hasil emisi gas buang - G. Gunawan; R.A. Novianto; R. Ayondya (Universitas Mataram, 2023)
The government is promoting the enforcement of over-dimensional and over-loading vehicles. Overloaded vehicles usually require a lot of power so it affects the results of exhaust emissions. This study aims to determine the results of emission tests by providing variations in load and speed on gasoline motorized vehicles, namely the Daihatsu Granmax Pick-Up 1.5 produced in 2014. The method used is experimental to determine the effect of independent variables (variations of load and speed) on the dependent variable (emissions exhaust gas). Variations of payload used are 0 kg, 735 kg, and 1200 kg with variations in speed of 0 km/hour, 10 km/hour, 20 km/hour, 30 km/hour, and 40 km/hour. The result of the experiment is that when the vehicle is unladen, with variations in speed, the Carbon monoxide (CO) and Hydro Carbon (HC) levels will be higher with a CO value of 0.83% and HC 121 ppm at a speed of 40 km/hour. When the vehicle is loaded according to GVW and given a variety of speeds, CO and HC levels increase with a CO value of 1.43% and HC 362 ppm at a speed of 40 km/hour. Meanwhile, if the vehicle is given a variation of speed with overload, the CO value rises to 3.30% and HC becomes 516 ppm at a top speed of 40 km/hour. So it can be concluded that the load variable and speed variations affect exhaust emissions and the largest exhaust emissions occur in overloaded vehicles.